Domperidone inhibits dengue virus infection by targeting the viral envelope protein and nonstructural protein 1 - Nuttapong Kaewjiw; Thanawat Thaingtamtanha; Damini Mehra; Wanida Chawnawa; Tanapan Prommool; Chunya Puttikhunt; Adisak Songjaeng; Kessiri Kongmanas; Panisadee Avirutnan; Prasit Luangaram; Chatchawan Srisawat; Sittiruk Roytrakul; et al. (Scientific Reports, 2025)
Abstract Dengue is a mosquito-borne disease caused by dengue virus (DENV) infection, which remains a major public health concern worldwide owing to the lack of specific treatments or antiviral drugs available. This study investigated the potential repurposing of domperidone, an antiemetic and gastrokinetic agent, to control DENV infection. Domperidone was identified by pharmacophore-based virtual screening as a small molecule that can bind to both the viral envelope (E) and the nonstructural protein 1 (NS1) of DENV. Molecular dynamics (MD) simulations and surface plasmon resonance (SPR) analysis were subsequently performed to determine specific interactions of domperidone with the DENV E and NS1 proteins and their binding affinity. Treatment of immortalized human hepatocyte-like cells (imHC) with domperidone could inhibit DENV production and NS1 secretion in a dose-dependent manner following infection with DENV serotype 2. These inhibitory effects were mediated by reduction in viral RNA replication and viral E and NS1 protein expression, but not by interference with virus entry into cells or NS1 oligomerization. The suppression of DENV production and NS1 secretion by domperidone was observed across all four DENV serotypes to varying degrees between different virus strains. The findings from our study suggest viral target-based repurposing of domperidone for modulating DENV.